Inverse Hysteresis and Ultrasmall Hysteresis Thin‐Film Transistors Fabricated Using Sputtered Dielectrics. (13th February 2017) - Zhao, Yudan; Huo, Yujia; Xiao, Xiaoyang; Wang, Yingcheng; Zhang, Tianfu; Jiang, Kaili; Wang, Jiaping; Fan, Shoushan; Li, Qunqing
Abstract : Large current hysteresis is observed in carbon nanotube (CNT) transistors and usually shows as a positive threshold voltage shift when the gate sweeping direction changes from positive to negative. This paper reports fabrication of inverse hysteresis CNT thin‐film transistors (TFTs) using magnetron sputtered oxide as a dielectric. Stacking of the sputtered dielectric with dielectrics deposited by other methods, such as atomic layer deposition, can effectively reduce or even eliminate the hysteresis. This can be explained as a combination of the effects of surface and interface trapped charges. Additionally, this hysteresis reduction method is widely compatible with various CNT‐TFT structures and types and is even suitable for MoS2 TFTs. The output characteristics and frequency responses of large and small hysteresis devices are compared and show that the small‐hysteresis inverter has lower distortion, and that its maximum operating frequency is nearly five times larger than that of TFTs with normal hysteresis. Abstract : Fabrication of inverse hysteresis carbon nanotube thin‐film transistors (TFTs) is reported using magnetron sputtered oxide as dielectric. Stacking the sputtered dielectric with other common dielectrics can reduce or eliminate the current hysteresis, which is also compatible with various structures and types, and even MoS2 TFTs. The maximum operating frequency of small‐hysteresis and normal‐hysteresis devices is compared and found to be five times difference.